Climate change and coastal vulnerability: application of vulnerability assessment methodologies in two coastal communities in South Africa - Griffiths, Chevon (Department of Environmental and Geographical Science, 2017)
Climate and environmental change is a phenomenon which is having a significant effect on human-ecological systems around the world. It is predicted to have a detrimental impact on certain groups and populations; among those most at risk are those who have the highest exposure and sensitivity to the climate and environmental changes and the lowest adaptive capacity. This includes coastal fishing communities and therefore necessitates action at a variety of scales in order to build the resilience of these individuals and groups to the predicted changes and their potential impacts. Vulnerability assessments (VAs) have been identified as an effective way to discover who is most vulnerable and to what threats or hazards. This is valuable as assistance can then be provided to the individuals, groups, regions or countries identified as most vulnerable. VAs can be conducted at a variety of scales and can be either quantitative or qualitative. This research project focused on vulnerability assessments conducted at the local level. These community-scale assessments are important as they are able to elicit finer-scale details, identify the greatest hazards and stressors, and conceptualize adaptation strategies that are locally-informed, context specific and targeted towards a specific community. The focus of this research project was to first assess the vulnerability of two coastal communities in South Africa, namely Doringbaai and St Helena Bay, using a suite of mixed methods which included focus group discussions, the review of secondary data, and key informant interviews. Secondly, this project aimed to assess the potential contribution of a 'rapid vulnerability assessment' (RVA) methodology, conducted in the same two coastal fishing communities, to gain information required to identify appropriate adaptation strategies in the context of climate and environmental change. The RVA is conducted as a workshop over a two-day period and may be followed by key informant interviews on the third day, if appropriate and required. This research sought to compare and contrast the information emanating from the RVA workshops with information obtained from the triangulation of mixed methods used in this study with respect to: key threats and stressors faced by the two small-scale fishing communities, identified environmental changes, impacts of these changes on fisher livelihoods, current coping strategies and potential adaptation strategies. Criteria for assessing the performance of the two different approaches were drawn from the literature and systematically documented. The outcome of the assessment showed that the RVA has value as a VA methodology and is able to identify locally relevant, potentially viable adaptation strategies. It is an effective approach for obtaining a good overview of the vulnerabilities of a community and is thus especially useful in under-resourced and data-poor regions. The conclusion was therefore that it is an exceptionally useful tool as a starting point for vulnerability assessments but can be enriched by combining it with other methods such as the review of secondary data, focus group discussions, surveys, questionnaires and key informant interviews. Furthermore, it is recommended that the RVA includes follow-up research and focuses on flexible adaptation strategies.